Sustainable office buildings : the impact of indoor environmental quality on the occupants / Sati Sekar Kinanthi - Kinanthi, Sati Sekar (2015)
Sustainable architecture has the well-being of both the environment and occupants as the center of its focus, where it benefits both simultaneously. This study addresses the impact of sustainable building on the occupants of office buildings in Malaysia. Embedded cross-case case study was conducted on 3 certified green buildings in Malaysia, where sustainable building design elements of the 3 buildings were studied. Surveys were distributed, and interviews were conducted on the occupants of the buildings to investigate the workability of the design, and how building occupants are affected by it. The result revealed that occupants of the selected sustainable office buildings perceive the IEQ condition of the sustainable buildings to affect their work performance, mood, sense of well-being and motivation in a positive manner. It was also found that it is the natural element incorporated in sustainable architecture that affect them positively, as well as moderate stimuli exuded by the IEQ of the green buildings. On the basis of the finding of this study, it was concluded that sustainable architecture has a positive impact on building occupants in the selected green office buildings in Malaysia. Keywords: Sustainable Office Buildings, Indoor Environmental Quality, Environmental Psychology